Vehicle-to-vehicle and vehicle-to-infrastructure communications a technical approach - Hu, Fei 1972- (Taylor & Francis, CRC Press, 2018)
This book focuses on the most critical technical aspects of vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) communications. It covers the smart city concept and architecture and explains how V2V and V2I fit into it. It describes the wireless communication protocols for V2V and V2I. It then explains the hardware design process for vehicle communication transceiver and antenna systems. It explains next-generation wireless technologies and their requirements for vehicle communication protocols. Case studies provide the latest V2V and V2I commercial design details. Finally, it describes how to implement vehicle communication protocol from practical hardware design angle.